Influence Coefficients for a Single Superficial Cracked Thick Cylinder Under Torsion and Bending Moments - Al-Moayed, Omar; Ali Kamil Kareem ,; AL EMRAN BIN ISMAIL,; SAIFULNIZAN BIN JAMIAN, (International Journal of Integrated Engineering, 2020)
In this paper, finite element analysis software, ANSYS, is used to calculate mode I, mode II and mode III SIFs for a single semi-elliptical surface crack located on a thick cylinder. Two crack positions were examined, external and internal cracks investigated under remote bending and torsion loading, separately. The ratio of the crack depth to crack length ranging from 0.4 to 1.2, while the ratio of crack depth to cylinder wall thickness vary between 0.2, 0.5 and 0.8, and the ratio of the cylinder’s internal radius to the cylinder’s wall thickness is 4. It is found for both bending and torsion, SIFs distributed symmetrically along the crack front, and the crack aspect ratio strongly affect the location of the maximum value. Generally, external cracks showed slightly higher SIFs than that of internal cracks. For bending loading, the effect of relative crack depth is higher than to that of torsion loading for the same crack configurations. For mode III, internal cracks showed a resistance to crack growth, dissimilar to external crack